How to create superior value in sustainable tourism: An exploratory study - Boksberger, P.; Carlsen, Jack (University of Technology Sydney, 2009)
Extensive research and practical implementation concerning the value of natural resources has thus far been conducted when one considers for example wildlife-, eco- and cultural tourism, however many of these values originate from industry and government perspective. This paper proposes the investment of minimal and sustainable resources in creating superior values from a customers’ perspective when visiting a national park. It proposes case studies in the Grand Canyon National Park (US), the Grampians National Park (OZ) and the Swiss National Park (CH) to highlight the significance of particular values of park visitors and how these values can be enhanced by using minimal resources to create superior value. A series of propositions and research process can be practically applied so as to further progress the research agenda relating to perceived value in sustainable tourism.